The Impact of Fertilizer Subsidy and Credit Program Policies on Farmers’ Well-Being in Southeast Sulawesi - Annisa Nur Rahmadani; Abdi; La Ode Jabuddin (International Journal of Technology and Education Research, 2026)
Farmer Exchange Rate ( NTP) is one of the indicators used to measure the level of farmers’ welfare. Agricultural subsidy policies are expected to improve farmers’ welfare through increasing agricultural productivity and farm income. This study aims to: (1) determine the dynamics of the Farmer Exchange Rate in Southeast Sulawesi, and (2) analyze the impact of subsidy policies on the Farmer Exchange Rate in Southeast Sulawesi. This research was conducted from October 2025 to March 2026. The population in this study consisted of all farmers in Southeast Sulawesi, while the samples included the Farmer Exchange Rate (NTP), fertilizer subsidies, and program credit subsidies. This research employed a quantitative descriptive approach using time series data from 2009–2029. Data analysis was conducted using multiple linear regression analysis with the Ordinary Least Square (OLS) method. The results of this study indicate that the effect of fertilizer subsidies and program credit subsidies on farmers’ welfare in Southeast Sulawesi is not uniform. Urea fertilizer, organic fertilizer subsidies, and People's Business Credit have a significant effect but tend to reduce the Farmer Exchange Rate, while SP-36 fertilizer subsidies significantly increase the Farmer Exchange Rate. Meanwhile, NPK fertilizer subsidies, and ZA fertilizer subsidies, do not have a significant effect on the Farmer Exchange Rate in Southeast Sulawesi